Analisis Terhadap Tindak Kekerasan Berbasis Gender Online Berbentuk Ancaman Penyebaran Konten Intim Non Consensual - Rahmawati; Kezia Hera Putri; Adila Fitriani; Lilik Prihatini S.H., M.H. (Sharia Journal and Education Center Publishing, 2023)
Abstract This journal discusses the crime of cybercrime or often called cybercrime, this journal aims so that we can learn more about cybercrime describing prohibited behavior as an Electronic Information and Transaction crime, Serna reviews the formulation of criminal sanctions for someone who commits online gender-based violence in the form of threats to spread non-consensual intimate content. Cases of cyber harassment or online harassment, namely harassment carried out through unwanted messages, attention, or contact and sending sexual messages via the internet and with acts of intimidation or threats and blackmail so that the victim complies with the perpetrator's request. This is included in online gender-based violence. Technology-facilitated online gender-based violence, like real-world gender-based violence, has the intent to harass the victim on the basis of sex or gender. Otherwise, the violence falls under the category of generalized cyber violence. Cases of online gender-based violence (GBV) also involve the distribution of non-consensual intimate content (NCII), including intimate videos referred to as